Eigenvalue Problem for Nonlinear Fractional Differential Equations with Integral Boundary Conditions - Guotao Wang; Sanyang Liu; Lihong Zhang (Abstract and Applied Analysis)
By employing known Guo-Krasnoselskii fixed point theorem, we investigate the eigenvalue interval for the existence and nonexistence of at least one positive solution of nonlinear fractional differential equation with integral boundary conditions.